Long-period high-flux high-temperature lead bismuth corrosion test device

By integrating oxygen concentration measurement and atmosphere control into a long-cycle, high-throughput, high-temperature lead-bismuth corrosion testing device, the problems of sealing reliability and experimental efficiency of existing devices have been solved. This device enables high-throughput testing and real-time monitoring of multiple parameters, accurately simulates the flow velocity environment inside the reactor, and provides a reliable evaluation of corrosion behavior.

CN120820480APending Publication Date: 2025-10-21NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511314295.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-15
Publication Date
2025-10-21

AI Technical Summary

Technical Problem

Existing high-temperature dynamic LBE corrosion testing equipment suffers from insufficient sealing reliability, low experimental efficiency, inability to simulate different flow rate environments within a reactor, and inaccurate oxygen concentration control, making it difficult to meet the needs of high-throughput screening of nuclear materials and simulation of realistic corrosion behavior.

Method used

Design a long-cycle, high-throughput, high-temperature lead-bismuth corrosion test device that integrates oxygen concentration measurement, atmosphere control, real-time acquisition of multiple parameters, and simulation of differentiated flow rates at multiple points. Employ a Bi/Bi2O3 oxygen sensor, a fully sealed magnetically driven stirring system, and modular fixtures to achieve high-throughput testing and real-time monitoring and control of multiple parameters.

Benefits of technology

It significantly improves experimental efficiency, supports parallel experiments on a large number of samples, accurately simulates different flow rate environments within the reactor, provides reliable evaluation of corrosion behavior, and provides a basis for predicting the corrosion resistance and lifespan of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120820480A_ABST
    Figure CN120820480A_ABST
Patent Text Reader

Abstract

The invention discloses a long-period high-flux high-temperature lead-bismuth corrosion test device, and relates to the technical field of lead-bismuth corrosion experiments.Sample rods of an annular array sample frame are evenly distributed around a stirring assembly in the circumferential direction, a modular clamp is arranged at the tail end of each sample rod, and a single clamp integrates multiple independent sample groove positions, so that a high-flux test is achieved; parallel corrosion tests of various materials and various working conditions can be completed in a single experiment, and compared with a traditional single-sample experiment, the material screening efficiency is greatly improved, and the experiment period is shortened; the corrosion behavior of the ODS-FeCrAl alloy under different doping proportions and different corrosion time is tested and analyzed under the oxygen control condition, the long-term service condition of a nuclear reactor structure material in a lead-bismuth coolant environment can be accurately simulated, and a reliable experimental basis is provided for corrosion resistance evaluation and service life prediction of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lead-bismuth corrosion experiments, and in particular relates to a long-period, high-throughput, high-temperature lead-bismuth corrosion testing device. Background Art

[0002] Liquid lead-bismuth (LBE) is considered a key coolant for advanced fourth-generation nuclear energy systems, such as lead-based fast reactors, due to its high boiling point, excellent heat transfer, and favorable neutron physics. However, LBE is highly corrosive to reactor structural materials, potentially causing surface dissolution, spalling, and even failure, posing a threat to the core's structural integrity and safe reactor operation. Previous studies have shown that controlling the oxygen concentration in LBE within a reasonable range allows for the rapid formation and maintenance of a stable self-healing oxide film on the material surface, effectively reducing the dissolution and corrosion of lead and bismuth on the structural materials. If the oxygen concentration is too low, a complete protective oxide film cannot form; if the oxygen concentration is too high, solid products such as lead oxide are likely to precipitate in the circuit, causing blockage and reduced heat transfer efficiency. Therefore, the oxygen concentration in LBE must be precisely controlled within a range that promotes the formation of a protective oxide film while preventing the deposition of excess oxides.

[0003] Therefore, the development of an integrated, high-precision liquid lead-bismuth alloy oxygen concentration monitoring and control device is of great significance for ensuring the corrosion resistance of lead-based fast reactor structural materials, extending service life, and ensuring the long-term safe and stable operation of the fourth-generation nuclear energy system. However, the current high-temperature dynamic LBE corrosion test device has significant bottlenecks: 1. The sealing reliability of the test device is insufficient. The traditional mechanical stirring shaft seal is not airtight in the high-temperature liquid lead-bismuth environment, making it difficult to achieve precise oxygen control; 2. The experimental efficiency is severely limited. Conventional reactors can only load 1-2 groups of samples at a time, resulting in a single material verification cycle of up to 3-6 months, which cannot meet the needs of high-throughput screening of nuclear materials; 3. The corrosion flow rate of materials at different locations in the reactor is different. This differentiated flow rate corrosion environment cannot be simulated in a uniform flow field experimental environment, which may lead to deviations in the prediction of the actual service behavior of the material; 4. Existing oxygen concentration monitoring and control methods mostly exist in the form of single sensors or discrete modules. It is often difficult to simultaneously achieve real-time measurement and precise control of oxygen concentration in a high-temperature, dynamic flow liquid lead-bismuth environment. Summary of the Invention

[0004] In response to the above technical problems, the present invention proposes a long-period, high-throughput, high-temperature lead-bismuth corrosion test device, which integrates oxygen concentration measurement, atmosphere control, real-time acquisition of multiple parameters, high-throughput testing, and multi-point differentiated flow rate simulation capabilities. It aims to solve the problem of sealing reliability, significantly improve experimental efficiency, support parallel experiments on large quantities of samples, and accurately simulate different flow rate environments in the reactor, thereby achieving more accurate simulation and reliable evaluation of the corrosion behavior of structural materials under oxygen control and real complex flow conditions.

[0005] A long-cycle, high-throughput, high-temperature lead-bismuth corrosion test device comprises a heating kettle, a stirring assembly and a sample rack located inside the heating kettle, and an air inlet and an air outlet provided on the heating kettle; During the test, the lead-bismuth solution is placed in the heating kettle and a constant high-temperature heating condition is provided. The sample is arranged around the stirring assembly. At the same time, the temperature and pressure in the heating kettle are respectively monitored by a thermocouple and a pressure sensor. The oxygen sensor monitors the oxygen content in the lead-bismuth solution. Ar / H2 gas or oxygen is introduced into the air inlet in a timely manner to control the oxygen content of the lead-bismuth solution. The air outlet is connected to the exhaust gas treatment device.

[0006] Preferably, the oxygen sensor is a Bi / Bi2O3 oxygen sensor, and is connected to a high-precision data acquisition system and visualization software installed on a computer for real-time monitoring, data recording and visualization of the oxygen content in the liquid lead-bismuth environment.

[0007] Preferably, the sample rack is an annular array sample rack, comprising a plurality of sample rods distributed circumferentially, a modular fixture is provided at the end of each sample rod, and a single fixture integrates a plurality of independent sample slots.

[0008] Preferably, the radial position of the sample rod is continuously adjustable.

[0009] Preferably, the modular fixture includes a hemispherical placement rack and a locking assembly detachably fixed thereto; the hemispherical placement rack is evenly distributed with a plurality of through holes, and an anti-drop cap is provided on the sample. The sample passes through the through holes from the inside of the hemispherical placement rack, and the anti-drop cap contacts the inner wall of the hemispherical placement rack; the locking assembly includes a fixing piece engaged and fixed with the hemispherical placement rack and a hemispherical pressure block contacting with the anti-drop cap. When the fixing piece is engaged with the hemispherical placement rack, the hemispherical pressure block presses the anti-drop cap to restrict its movement.

[0010] Preferably, the contact surface between the anti-dropping cap and the inner wall of the hemispherical placement rack and the contact surface between the anti-dropping cap and the hemispherical pressing block are both matching arc surfaces.

[0011] Preferably, alumina ceramics are used to isolate the samples.

[0012] Preferably, the stirring assembly includes a fully sealed magnetic drive system, a connecting shaft that rotates under the drive of the magnetic drive system, and a propeller fixed to the end of the connecting shaft.

[0013] Preferably, the fully sealed magnetic drive system adopts a magnetic coupling design of an external permanent magnet rotor and an internal impeller, and realizes torque transmission by generating a strong magnetic field through samarium cobalt permanent magnets.

[0014] Beneficial effects of the present invention: 1. The sample rods of the annular array sample holder are evenly distributed around the stirring assembly. A modular fixture is set at the end of each sample rod. A single fixture integrates multiple independent sample slots to achieve high-throughput testing. A single experiment can complete parallel corrosion testing of multiple materials and multiple working conditions. Compared with traditional single-sample experiments, this greatly improves material screening efficiency and shortens experimental cycles. 2. Alumina ceramic sheets with a thickness of 0.8-1.5 mm are embedded between samples of different materials to completely isolate physical contact and avoid cross contamination.

[0015] 3. Through the continuous adjustment of the radial position of the sample rod, the corrosion environment in the reactor from the low-speed flow area of ​​the tube wall to the high-speed flow area of ​​the impeller is simulated; 4. Under oxygen-controlled conditions, the corrosion behavior of ODS-FeCrAl alloy at different doping ratios and different corrosion times is tested and analyzed, which can accurately simulate the long-term service conditions of nuclear reactor structural materials in a lead-bismuth coolant environment and provide a reliable experimental basis for material corrosion resistance evaluation and life prediction. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a schematic structural diagram of the long-period, high-throughput, high-temperature lead-bismuth corrosion test device disclosed in the present invention; Figure 2 This is a top view of the circular array sample holder; Figure 3 This is a side view of the circular array sample holder; Figure 4 Schematic diagram of the through hole of the hemispherical placement rack; Figure 5 Schematic diagram of modular fixture structure; Figure 6 is a schematic diagram of the corrosion morphology of FeCrAl alloy at different corrosion times. Figures 6(a) to 6(d) Corresponding to FeCrAl alloy samples 1 to 4 respectively; Figure 7 shows the XRD patterns of FeCrAl alloy at different corrosion times. Figures 7(a) to 7(d) Corresponding to FeCrAl alloy samples 1 to 4 respectively; Figure 8 shows the SEM morphology of the FeCrAl alloy sample 1 at different corrosion times. Figures 8(a) to 8(d)Corresponding to corrosion time of 500h, 1000h, 1500h and 2000h respectively; Figure 9 shows the SEM morphology of the FeCrAl alloy sample 3 at different corrosion times. Figures 9(a) to 9(d) Corresponding to corrosion time of 500h, 1000h, 1500h and 2000h respectively; Figure 10 shows the cross-sectional microstructure and element line scans of sample 3 at different sampling times. Figures 10(a) to 10(d) They correspond to sampling times of 500h, 1000h, 1500h, and 2000h respectively; Figure 11 EDS element mapping of the cross section of the alteration layer. DETAILED DESCRIPTION

[0017] The present invention will be described in further detail below with reference to the accompanying drawings and specific embodiments. The embodiments of the present invention are provided for purposes of illustration and description and are not intended to be exhaustive or to limit the invention to the disclosed forms. Many modifications and variations will be apparent to those skilled in the art. The embodiments are chosen and described to better illustrate the principles of the invention and its practical application, and to enable those skilled in the art to understand the invention and design various embodiments with various modifications suitable for specific applications. Example

[0018] A long-cycle, high-throughput, high-temperature lead-bismuth corrosion test device, such as Figure 1 As shown, it includes a heating kettle 1, a stirring assembly 2 and a sample holder 3 located inside the heating kettle, an air inlet 4 and an air outlet 5 provided on the heating kettle, and an oxygen sensor 8 placed in the high-temperature lead-bismuth solution for monitoring the oxygen content in the liquid lead-bismuth environment. Figure 1 It can be seen that the gas inlet 4 directly passes the gas into the liquid lead bismuth 6 through a pipeline.

[0019] The oxygen sensor described here is a Bi / Bi2O3 oxygen sensor connected to a high-precision data acquisition system and computer-installed visualization software. This sensor is used for real-time monitoring, data recording, and visualization of oxygen content in a liquid lead-bismuth environment. The Bi / Bi2O3 oxygen sensor consists of a solid electrolyte, a reference electrode, a working electrode, an auxiliary electrode, and a sealing material. The solid electrolyte is a cylindrical structure made of sintered zirconium oxide (YSZ, stabilized with 8 mol% yttria) powder (diameter and thickness are subject to design adjustments). The operating temperature is typically 600-800°C (YSZ exhibits high oxygen ion conductivity within this temperature range). The reference electrode is composed of a mixture of Bi and Bi2O3 (molar ratio approximately 95:5). At high temperatures (>500°C), a liquid Bi-Bi2O3 eutectic system is formed (Bi melting point 271°C, Bi2O3 melting point 825°C, eutectic temperature approximately 480°C). This serves as a reference phase for oxygen partial pressure, whose equilibrium oxygen partial pressure is determined by the inherent thermodynamic properties of Bi2O3 and can be considered constant. The working electrode is made of metallic Mo (Mo), which has high chemical stability at high temperatures and good compatibility with liquid LBE. It is in direct contact with the liquid LBE and serves as a sensitive electrode, responding to changes in the oxygen partial pressure within the LBE. The auxiliary electrode, made of the same material as the working electrode, Mo or another inert metal (Pt is used in this example), serves to close the measurement loop or compensate for electrode polarization. The core of the Bi / Bi2O3 oxygen sensor is based on the oxygen ion migration and electromotive force generated by the difference in oxygen partial pressure between the two sides. The Nernst equation quantifies the relationship between the electromotive force and the oxygen partial pressure difference, enabling oxygen content monitoring.

[0020] The heating vessel was constructed of 316L stainless steel. Prior to the corrosion test, liquid lead-bismuth alloy (LBE) containing 44.5 wt.% Pb and 55.5 wt.% Bi was added to the vessel. Prior to sample insertion, the LBE temperature was maintained at 550°C. An oxygen sensor consisting of a Bi / Bi2O3 reference electrode and a Mo working electrode was used to measure the dissolved oxygen concentration in the liquid lead-bismuth. The oxygen sensor was calibrated by measuring the voltage under both saturated and oxygen-free conditions. The relationship between the voltage and oxygen content was then fitted. Ar / H2 gas was used to control the oxygen content, resulting in a stable output voltage of approximately 490 mV.

[0021] The samples are arranged around the stirring assembly to increase the loading capacity of samples from the same batch, and the temperature and pressure in the heating kettle are monitored respectively by a thermocouple and a pressure sensor.

[0022] In order to increase the loading capacity of samples in the same batch, the sample rack 3 is a ring array sample rack, such as Figure 2 、 Figure 3 As shown, it includes multiple sample rods 31 distributed circumferentially, and a modular clamp 32 is set at the end of each sample rod. A single clamp integrates multiple independent sample slots.

[0023] In order to simulate the corrosion environment from the low-speed flow area of ​​the tube wall to the high-speed flow area of ​​the impeller in the reactor, the radial position of the sample rod 31 is continuously adjustable. For specific implementation, see Figure 2 The holder 33 of the sample rod 31 is provided with a plurality of radial slots 34. The sample rod 31 passes through the radial slots 34 and is fastened to the holder 33 at its top end by a fastener 35. The diameter of a single fastener 35 is larger than the width of a radial slot 34, and the length of a radial slot 34 is larger than the diameters of two fasteners 35. This allows for radial adjustment between the sample rods 31. In this embodiment, the adjustable range is 50-120 mm.

[0024] More specifically, the modular fixture 32 includes a hemispherical placement frame 321 and a locking assembly 322 detachably fixed thereon; the hemispherical placement frame 321 is evenly distributed with a plurality of through holes 323, see Figure 4 The sample 7 is provided with an anti-drop cap 324. The sample 7 passes through the hole 323 from the inside of the hemispherical placement frame 321. The anti-drop cap 324 contacts the inner wall of the hemispherical placement frame 321. Figure 5 The locking assembly 322 includes a fixing member 325 that is engaged with the hemispherical placement frame 321 and a hemispherical pressing block 326 that contacts the anti-drop cap 324. When the fixing member 325 is engaged with the hemispherical placement frame 321, the hemispherical pressing block 326 presses the anti-drop cap 324 to restrict its movement. Figure 5 This modular fixture maximizes the use of space, making it easier to load more samples, and the loading and locking methods are easy to operate.

[0025] To better secure the samples, the contact surfaces of the cap with the inner wall of the hemispherical mounting bracket and the hemispherical pressure block are all matched curved surfaces. Alumina ceramic can also be used to isolate samples to prevent cross-contamination of large batches of samples. The alumina ceramic fixing method can be referenced in the sample and will not be further described here.

[0026] The stirring assembly 2 comprises a fully sealed magnetic drive system 21, a rotating connecting shaft 22 driven by the system, and a propeller 23 fixed to the end of the connecting shaft 22. The fully sealed magnetic drive system utilizes a magnetic coupling design between an external permanent magnet rotor and an internal impeller. This system utilizes samarium-cobalt permanent magnets to generate a strong magnetic field for torque transmission, completely eliminating the risk of mechanical shaft seal leakage in 550°C LBE. The impeller rotates at 600 rpm, driving the LBE flow and accurately simulating the dynamic operating conditions of a lead-cooled fast reactor coolant.

[0027] The following is a dynamic lead-bismuth corrosion test on ODS-FeCrAl alloy using the long-cycle, high-throughput, high-temperature lead-bismuth corrosion test apparatus provided by the present invention. This embodiment is described using a modular fixture with four independent sample slots as an example. The sample composition is shown in Table 1. The sample is placed in a lead-bismuth corrosion reaction heating kettle with a lead-bismuth flow rate of 1 m / s and a temperature of 550°C. The final oxygen content is controlled at 1×10 -4 wt.%~5×10 -4 Reactions were performed at 500, 1000, 1500, and 2000 wt.% concentrations, with samples removed at 500, 1000, 1500, and 2000 h, respectively. The LBE was not replaced until the experiment was complete. Using an adjustable ring array sample holder and modular fixture design, a single experiment can simultaneously remove 16 sets of samples (four materials at four time points), completing the task required by traditional 16 independent experiments and significantly improving high-throughput material screening.

[0028] Table 1

[0029] 1. Overall morphology of the sample after corrosion Figures 6(a) to 6(d) This is the overall morphology of ODS-FeCrAl alloy samples 1~4 doped with different contents of Y2O3 after different corrosion times. It can be seen that the samples are generally intact without any damage or missing corners. The overall color is gray and black, and is partially covered with yellow flakes.

[0030] Comparison with the literature reveals that the yellow portion is lead-bismuth oxidation products, remaining attached to the oxide film. The oxide film exhibits a grayish-dark color, consistent with the characteristics of iron oxide products. For Sample 1, the surface gradually darkened and corrosion products increased with corrosion time. In particular, at 2000 h, obvious corrosion marks appeared on the surface, indicating that the oxide film gradually failed under long-term lead-bismuth corrosion and exhibited poor corrosion resistance. Sample 4 exhibited good corrosion resistance within 500 and 1000 h, but as corrosion time extended to 1500 and 2000 h, a large number of corrosion products and even localized flaking appeared on the surface, suggesting that excessive Y2O3 addition may lead to local stress concentration or grain boundary segregation, compromising the alloy's corrosion resistance.

[0031] 2. XRD test XRD test was performed on the corroded samples. Figures 7(a) to 7(d) The XRD patterns of samples 1–4, doped with different amounts of Y₂O₃, show the phase changes after different lead-bismuth corrosion times (500 h, 1000 h, 1500 h, and 2000 h). Analyzing the evolution of XRD peaks reveals the phase composition changes during the corrosion process and the formation mechanism of the oxide film.

[0032] At 500 h, characteristic peaks of Fe₃O₄ (spinel iron oxide) and Fe(Cr,Al)₂O₄ (Cr- and Al-rich spinel structure) appeared in the XRD pattern, indicating that an oxide film had begun to form on the material surface. The addition of Y₂O₃ likely promoted the formation of the Fe(Cr,Al)₂O₄ phase, improving the stability of the oxide film. The alloy matrix peaks were still evident, indicating that the oxide layer was thin in the initial stages of corrosion and did not completely cover the substrate.

[0033] As corrosion time increases to 1000 and 1500 h, the diffraction peak intensities of Fe₃O₄ and Fe(Cr,Al)₂O₄ increase, indicating further thickening of the oxide film. The formation of Fe(Cr,Al)₂O₄ indicates oxidation of Al and Cr, forming a stable spinel structure. The presence of this phase helps to improve the density of the oxide film and reduce the corrosion of the Pb-Bi melt. The matrix peak intensity decreases slightly, indicating that the oxide layer gradually increases in thickness, which has a certain shielding effect on the matrix diffraction signal.

[0034] At 2000 h, the peak intensities of the Fe₃O₄ and Fe(Cr,Al)₂O₄ phases further increased, indicating that the oxide layer continued to grow and stabilize. The matrix peak further weakened, indicating that the oxide film essentially covered the surface, protecting the substrate from further erosion by the Pb-Bi melt. The presence of Fe₃O₄ in a long-term corrosive environment may affect the stability of the oxide film, leading to localized spalling or cracking, but the formation of Fe(Cr,Al)₂O₄ helps improve the film's stability.

[0035] 3. Surface oxide film analysis Figures 8 and 9 are SEM images of the sample surface at different corrosion times under the condition of a lead-bismuth relative flow rate of 1m / s. Figure 8 is the SEM image of sample 1, and Figure 9 is the SEM image of sample 3. Taking the sample (doped with 0.6 wt.% Y2O3) as an example, it can be seen that Figures 9(a) to 9(d) Corresponding to samples at 500 h, 1000 h, 1500 h, and 2000 h, it can be clearly seen that protruding spherical compound structures appear on the surface of the samples. In Figure 9(a), the surface of the sample is covered with a small amount of compounds; in Figure 9(b), it begins to gradually increase; in Figures 9(c) and 9(d), as time goes by, more compounds are covered on the surface of the sample.

[0036] 4. Cross-section analysis Taking FeCrAl alloy sample 3 as an example, the cross section of its oxide film / substrate interface was analyzed. Figures 10(a) to 10(d)The cross-sectional microstructure morphology and element line scans of sample 3 at sampling times of 500h, 1000h, 1500h, and 2000h, respectively. The horizontal coordinate Positionion of the scan represents the path coordinate of the electron beam scanning on the sample surface, reflecting the position of the analyzed area in the two-dimensional plane. The vertical coordinate Atomic Fraction represents the ratio of the number of atoms of the target element at the scanning position to the total number of atoms, which is an atomic-level quantitative indicator of the element content.

[0037] from Figures 10(a) to 10(d) As can be seen in the graph, the oxide film on the FeCrAl alloy surface undergoes a significant evolutionary process with increasing oxidation time. During the oxidation period of 500 to 1000 h, a continuous and dense oxide film forms on the surface, effectively preventing further corrosion of the substrate by environmental factors. When the oxidation time is extended to 1500 to 2000 h, the oxide film gradually evolves into a bilayer structure, indicating changes in the oxidation kinetics and phase composition of the oxide film. Simultaneously, the overall thickness of the oxide film increases over time, from 15.03 μm at 500 h to 32.01 μm at 1000 h, and then reaches 37.97 μm and 40.05 μm at 1500 and 2000 h, respectively, indicating that the growth trend of the oxide film gradually stabilizes.

[0038] 5. Phase and composition analysis of different oxide layer regions Analysis shows that the composition of the oxide film is significantly different at different depths. Figure 11 Semi-quantitative energy dispersive spectrometer (EDS) analysis revealed that region (I) of the oxide film is primarily enriched in Fe, Cr, Al, and O, with trace amounts of Pb and Bi detected. This suggests that the oxide film can, to a certain extent, prevent the penetration of the lead-bismuth (LBE) medium, thereby improving the alloy's corrosion resistance in LBE environments. Combined with the XRD analysis previously reported, region (I) is primarily composed of Fe(Cr,Al) spinel compounds. Its dense structure effectively protects the substrate during oxidation, slowing further oxidation and element diffusion.

[0039] Furthermore, quantitative elemental analysis of region (II) reveals relatively low Fe and Cr contents, while high Al and O contents, indicating that this layer is rich in Al₂O₃. Based on XRD analysis and elemental composition, it is speculated that the oxide layer in this region is likely composed primarily of incompletely oxidized Al₂O₃, indicating that Al plays a significant role in the oxidation process. Due to its low ion diffusion rate and high thermodynamic stability, Al₂O₃ forms a relatively stable protective layer in high-temperature oxidizing environments, effectively improving the oxidation resistance and LBE corrosion resistance of the FeCrAl alloy.

[0040] In summary, through the long-cycle, high-throughput, high-temperature lead-bismuth corrosion test device provided by the present invention, the corrosion behavior of ODS-FeCrAl alloy at different doping ratios and different corrosion times was tested and analyzed under oxygen-controlled conditions. The results show that the device can accurately simulate the long-term service conditions of nuclear reactor structural materials in a lead-bismuth coolant environment, and provide a reliable experimental basis for material corrosion resistance evaluation and life prediction.

[0041] Obviously, the embodiments described are only some of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without making any creative work should fall within the scope of protection of the present invention.

Claims

1. A long-period, high-throughput, high-temperature lead-bismuth corrosion test device, characterized in that: It comprises a heating kettle, a stirring assembly and a sample rack located inside the heating kettle, and an air inlet and an air outlet arranged on the heating kettle; During the test, the lead-bismuth solution is placed in the heating kettle and a constant high-temperature heating condition is provided. The sample is arranged around the stirring assembly. At the same time, the temperature and pressure in the heating kettle are respectively monitored by a thermocouple and a pressure sensor. The oxygen sensor monitors the oxygen content in the lead-bismuth solution. Ar / H2 gas or oxygen is introduced into the air inlet in a timely manner to control the oxygen content of the lead-bismuth solution. The air outlet is connected to the exhaust gas treatment device.

2. The long-period high-throughput high-temperature lead-bismuth corrosion test device according to claim 1 is characterized in that: The oxygen sensor is a Bi / Bi2O3 oxygen sensor, which is connected to a high-precision data acquisition system and visualization software installed on a computer for real-time monitoring, data recording and visualization of the oxygen content in a liquid lead-bismuth environment.

3. The long-period high-throughput high-temperature lead-bismuth corrosion test device according to claim 1, characterized in that: The sample rack is an annular array sample rack, comprising a plurality of sample rods distributed circumferentially, a modular fixture is provided at the end of each sample rod, and a single fixture integrates a plurality of independent sample slots.

4. The long-period high-throughput high-temperature lead-bismuth corrosion test device according to claim 3, characterized in that: The radial position of the sample rod is continuously adjustable.

5. The long-period high-throughput high-temperature lead-bismuth corrosion test device according to claim 3, characterized in that: The modular fixture includes a hemispherical placement frame and a locking assembly that is detachably fixed thereto; the hemispherical placement frame is evenly distributed with a plurality of through holes, and an anti-drop cap is provided on the sample. The sample passes through the through holes from the inside of the hemispherical placement frame, and the anti-drop cap abuts against the inner wall of the hemispherical placement frame; the locking assembly includes a fixing piece that is engaged and fixed with the hemispherical placement frame and a hemispherical pressure block that abuts against the anti-drop cap. When the fixing piece is engaged with the hemispherical placement frame, the hemispherical pressure block presses the anti-drop cap to restrict its movement.

6. The long-period high-throughput high-temperature lead-bismuth corrosion test device according to claim 5, characterized in that: The contact surface between the anti-dropping cap and the inner wall of the hemispherical placement rack and the contact surface between the anti-dropping cap and the hemispherical pressing block are both matching arc surfaces.

7. The long-period high-throughput high-temperature lead-bismuth corrosion test device according to claim 5, characterized in that: Alumina ceramics were used to isolate the samples.

8. The long-period high-throughput high-temperature lead-bismuth corrosion test device according to claim 1, characterized in that: The stirring assembly includes a fully sealed magnetic drive system, a connecting shaft that rotates under the drive of the magnetic drive system, and a propeller fixed to the end of the connecting shaft.

9. The long-period high-throughput high-temperature lead-bismuth corrosion test device according to claim 8, characterized in that: The fully sealed magnetic drive system adopts a magnetic coupling design of an external permanent magnet rotor and an internal impeller, and achieves torque transmission by generating a strong magnetic field through samarium cobalt permanent magnets.